2016
DOI: 10.1080/00063657.2015.1135104
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for deleterious effects of harness-mounted satellite transmitters on Saker FalconsFalco cherrug

Abstract: 2016) Evidence for deleterious effects of harness-mounted satellite transmitters on Saker Falcons Falcocherrug, Bird Study, 63:1, 96-106, Capsule This study identifies lethal and sub-lethal effects associated with the deployment of harnessmounted satellite transmitters on a large falcon species. Aims We examined the effect of harness-mounted satellite transmitters and patagial tags on survival, behaviour and physical health of adult Saker Falcons. Methods We compared breeding turnover of Saker Falcons deployed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
(42 reference statements)
1
9
0
6
Order By: Relevance
“…For Central Europe, for example, it is shown that regardless of the place of origin, almost all juvenile Saker Falcons migrate to the south-west (an average 210°) (Prommer et al, 2012). For the populations of Central Mongolia, with a wide post-fledging dispersal, migrations of Sakers are mainly directed to the south-west (Potapov et al, 2002;Dixon et al, 2017), which is determined by the optimum wintering conditions for Saker Falcons in Tibet.…”
Section: первая осенняя миграцияsupporting
confidence: 64%
See 3 more Smart Citations
“…For Central Europe, for example, it is shown that regardless of the place of origin, almost all juvenile Saker Falcons migrate to the south-west (an average 210°) (Prommer et al, 2012). For the populations of Central Mongolia, with a wide post-fledging dispersal, migrations of Sakers are mainly directed to the south-west (Potapov et al, 2002;Dixon et al, 2017), which is determined by the optimum wintering conditions for Saker Falcons in Tibet.…”
Section: первая осенняя миграцияsupporting
confidence: 64%
“…Максимальная скорость по анализу 2-6 часовых промежутков у разных птиц ва-of the Mongolian Saker Falcons in Tibet: MCP 70% varied from 3 km 2 to 18.5 thousand km 2 (Dixon et al, 2017). The areas of home ranges in Tibet calculated as Kernel 50%, varied from 3.6 to 131.5 km 2 , mean 36.98 km 2 (Dixon et al, 2017), which is slightly lower than the area of home ranges of our birds that wintered in Kazakhstan, North-West China and Mongolia (36.1-132.81, mean 79.82±35.83 km 2 ). It is definite, that the area of home ranges depends on the availability and abundance of prey, and it is probably higher in Tibet due to the high density and concentration of the Black-Lipped Pika (Ochotona curzoniae) colonies.…”
Section: первая осенняя миграцияmentioning
confidence: 87%
See 2 more Smart Citations
“…Classically, individual identification relies on visible markers such as leg bands (Lincoln 1921), patagial tags (Anderson 1963) and remote radio transmitter devices such as short-range VHF or satellite-received transmitters (Varland et al 2007;Diemer et al 2014). These marking techniques have greatly facilitated the estimation of survival, but they can be labor intensive, time consuming and costly, and potentially have deleterious impacts on the behavior, physiology and survival of individuals through catching and handling and from the equipment deployed (Klugman et al 1993;Booms et al 2011;Peniche et al 2011;Dixon et al 2016).…”
Section: Introductionmentioning
confidence: 99%